Akuntabilitas Pemerintah Desa dalam Pengelolaan Alokasi Dana Desa - Surya Adi Tama, Putu; Wirama, Dewa Gede (E-Jurnal Akuntansi, 2020)
This study aims to identify, analyze, and describe the accountability of village governments in the management of village fund allocation in 2018 budget year which includes the planning, implementation and accountability phases in Tumbu Village, Karangasem, so that it can be used by the government so that government organizations can run well, and efficiently. In this study, qualitative approach with descriptive analysis method was used. The results of the research indicate that administratively the Tumbu Village Government has been transparent and accountable in every stage of planning, implementation, and accountability of village fund allocation. However, the village government still finds it difficult to prepare the Budget Realization Report for the Implementation of the Budget Year 2018, so that the sub-district government needs to provide assistance and guidance. Keywords: Accountability; Village Government; Management; Village Fund Allocation; Planning;  Implementation.